If f(x) = 5x + 7 and g(x) = -2x – 4 Find f(g(x)) = -10x + [?] Enter​

Question

If f(x) = 5x + 7 and g(x) = -2x – 4 Find f(g(x)) = -10x + [?] Enter​

in progress 0
Vân Khánh 7 months 2021-08-07T16:09:29+00:00 1 Answers 2 views 0

Answers ( )

    0
    2021-08-07T16:10:31+00:00

    Answer:

    f(g(x)) =  -10x -13

    Step-by-step explanation:

    Given

    f(x) = 5x + 7

    g(x) = -2x - 4

    Required

    Find f(g(x))

    This is calculated as:

    f(x) = 5x + 7

    Substitute g(x) for x

    f(g(x)) =  5(f(g(x)) + 7

    Substitute g(x) = -2x - 4

    f(g(x)) =  5(-2x - 4) + 7

    Open bracket

    f(g(x)) =  -10x - 20 + 7

    f(g(x)) =  -10x -13

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )